Pencegahan Computer Vision Syndrome - Syarifah Rohaya; Hafizh Shidqi (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Currently in the modern era, the development of science and technology is very rapid. More and more new technologies are emerging. Electronics make up a large part of everyday life at home, at work, and during leisure time. The use of desktops, laptops, computers, tablets, smart phones and reading from electronic devices has been used by everyone. While most of these uses of electronics can make life easier, there can also be negative effects. Long-term use can have an adverse effect on eye health known as computer vision syndrome.